Reactive Aggression Affects Response Inhibition to Angry Expressions in Adolescents: An Event-Related Potential Study Using the Emotional Go/No-Go Paradigm - Sun, Lijun; Li, Junyi; Niu, Gengfeng; Zhang, Lei; Chang, Hongjuan (Frontiers in Psychology, 2020)
Although it is well established that response inhibition to angry expressions is impaired among reactively aggressive adolescents, the cognitive processes underlying this effect remain unclear. The main goal of our study was to investigate the time course of response inhibition to angry expressions in reactively aggressive adolescents compared to controls. In total, 23 reactively aggressive adolescents and 23 control adolescents were recruited to participate in an ERP study measuring response inhibition to angry expressions with an emotional Go/No-go paradigm. The results showed that when presented angry or happy expressions, reactively aggressive adolescents showed a smaller No-go P3 effect than the control group. These results indicate that response inhibition to angry expressions in reactively aggressive adolescents is impaired at the later stage of the actual inhibitory control. The characteristics of response inhibition to happy expressions in reactively aggressive adolescents are similar to those in response to angry expressions.